Kariera akademicka, kobiety i Uniwersytet Poznański. Konteksty historyczno-teoretyczne - Gromkowska-Melosik, Agnieszka (Studia Edukacyjne, 2019)
The history of women`s acces to an academic career is an excellent exemplification of all theories and concepts of gender inequality. It can be said that it was within the Academy that the concepts of „glass ceiling” or „sticky floor” found their very radical realizations. It is also here that gender inqualities overlapped with racial, class and ethnic inqualities. In genear, all authors emphasize – both in relation to the past and the present – „the lack of adequate representation of women in the professoriate” and in the exercise of academic authority. There are many theories trying to explain this imblance. In addition to strongly coservative claims that different career paths result from biological „developmental” differences of both sexes, there are also those that emphasize socio-cultural factos. The purpose of my text is not to analyse the field of academic careers for men and women, nor to reconstruct the theory in this area, but to attempt to present selected historical contexts, mainly in the context of the University of Poznań in a slightly broader analytical context.